ankA: an Ehrlichia phagocytophila Group Gene Encoding a Cytoplasmic Protein Antigen with Ankyrin Repeats - Caturegli, Patrizio (American Society for Microbiology, 2000)
Human granulocytic ehrlichiosis (HGE) is a potentially fatal, tick-borne disease caused by a bacterium related or identical to Ehrlichia phagocytophila. To identify and characterize E. phagocytophila group-specific protein antigen genes, we prepared and screened HGE agent and Ehrlichia equi genomic DNA expression libraries using polyclonal equine E. equi antibodies. Two clones, one each from HGE agent and E. equi, that were recognized specifically by antibodies to the E. phagocytophila group ehrlichiae had complete open reading frames of 3,693 and 3,615 nucleotides, respectively. The two clones were 96.6% identical and predicted a protein with at least 11 tandemly repeated ankyrin motifs. Thus, the gene was named ank (for ankyrin). When the encoded protein, named AnkA, was expressed in Escherichia coli, it was recognized by antibodies from rabbits and mice immunized with the HGE agent, sera from humans convalescent from HGE, and sera from horses convalescent from HGE and E. equi infection. Monospecific AnkA antibodies reacted with proteins in HGE agent immunoblots, and AnkA monoclonal antibodies detected cytoplasmic antigen in E. phagocytophila group bacteria and also detected antigen associated with chromatin in infected but not uninfected HL-60 cell cultures. These results suggest that this Ehrlichia protein may influence host cell gene expression.